Mechanochemical synthesis of La0.67Ce0.21Nd0.08Pr0.04Ni5 intermetallic compound - Blanco, Maria Valeria (2013)
The mechanochemical synthesis of a La0.67Ce0.21Nd0.08Pr0.04Ni5 intermetallic is studied. The intermetallic is synthesised from a mixture of LaNi5 and La0.25Ce0.52Nd0.17Pr0.06Ni5. The processes controlling the mechanical alloying are characterised as a function of integrated milling time (tm). Effects of fracture and cold welding on the sample are identified by scanning electron microscopy. Compositional, microstructural and structural changes are analysed by energy dispersive spectroscopy and X-ray diffraction. The powder obtained has a particle size distribution of 9 ± 1 lm with an average crystallite size of 370 ± 10 Å and strain >10%. The intermetallic compound is annealed in Ar to increase crystallite size and to release strain. The structure is refined by the Rietveld method. Cell parameters are a = 4.982(2) Å and c = 3.980(9) Å, respectively. The advantage of the synthesis method using intermetallics instead of metals/alloys is discussed along with the characteristics of the powder obtained.